PAIR PROGRAMMING IMPROVES STUDENT RETENTION, CONFIDENCE, AND PROGRAM QUALITY. (Communications of the ACM, 2006)
The article discusses pair programming, which requires cooperation between programmers while developing software. One programmer actively creates code and controls the computer input systems while the other reviews the data and analyzes its tactical and strategic deficiencies. After a designated amount of time the two switch roles. Pair programming in an educational setting produces more proficient and confident programmers and could help increase female representation in the field of computer programming.